Effectiveness Theory And Practice Model Swimming - Raswin Raswin; Achmad Sofyan Hanief; Abdul Syukur (Universitas PGRI Palembang, 2022)
Theoretical understanding and practice in swimming learning still cannot be integrated scientifically in student learning. So it is necessary to have a theoretical and training model to improve swimming ability. The aim is to find out how effective the theoretical and exercise models are designed for experiments on 75 students. The experimental method used the control group and the experimental group. Theory and practice used online and face-to-face learning with an analysis of the results of the t-test starting with the pre-test and ending with the post-test. The results showed that there was a significant difference between the experimental group and the control group with scorest-test for Equality of Means. From this column, the value of t count = 3.638, df = 58, so the table = 2.002 is obtained. When compared, the value of t count > t table and sig (2 tailed) or p-value = 0.001 <0.05 or H0 is rejected. Even with sometimes limitations to the use of technology such as the need for maintenance and loss of connectivity, teaching online (web-based) nevertheless empowers students and maximizes their learning. Students in the study reported their liking for being able to proceed at their own pace